2015
DOI: 10.4103/0973-1229.153338
|View full text |Cite
|
Sign up to set email alerts
|

Changing Medical Students′ Attitudes to Psychiatry through Newer Teaching Techniques

Abstract: The significance of mental health in the entire health scenario has increased. However, the representation of psychiatry in the current MBBS curriculum for undergraduate students in India still remains much less than desirable. Further, stigmatising attitudes lessen these future doctors’ ability to detect and manage patients with psychological problems despite adequate knowledge about psychiatry. Students believe that psychiatrically ill patients are unpredictable and can be dangerous to others. Some feel that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…In the meantime, widely implemented methods combining theory and practice with concepts such as problem-based learning or bedside-teaching ( 50 , 51 ) or other approaches (e.g., psychiatry electives, summer institutes, exchange programs, small group teaching, simulated patients, using movies, multidisciplinary seminars, integrated teaching, attitude questionnaires, and objective structured clinical examinations, etc.) could be promising in further improving attitudes toward psychiatry ( 23 , 52 ), interest in psychiatry, and/or career choice ( 19 , 26 ). In particular, scenario-based learning in different settings, such as primary care or general hospitals, could prepare medical students for a potential future in psychiatry ( 53 , 54 ), even if findings on the setting of clinical experience with psychiatry are contradictory ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the meantime, widely implemented methods combining theory and practice with concepts such as problem-based learning or bedside-teaching ( 50 , 51 ) or other approaches (e.g., psychiatry electives, summer institutes, exchange programs, small group teaching, simulated patients, using movies, multidisciplinary seminars, integrated teaching, attitude questionnaires, and objective structured clinical examinations, etc.) could be promising in further improving attitudes toward psychiatry ( 23 , 52 ), interest in psychiatry, and/or career choice ( 19 , 26 ). In particular, scenario-based learning in different settings, such as primary care or general hospitals, could prepare medical students for a potential future in psychiatry ( 53 , 54 ), even if findings on the setting of clinical experience with psychiatry are contradictory ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that psychiatry education has proved to be effective in changing the attitude of medical students toward mental illness; however, there is urgent need to review the current curriculum also[ 18 ] and to incorporate newer teaching methods to develop the attitudes of empathy, respect, understanding, etc., and to reduce stigma toward psychiatry resulting in better patient care. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%
“…We identified facilitators (patient interaction, outpatient department observation and teaching, demonstration of signs, case presentation and discussion, evening posting, observation of clinical work, use of anecdotes while teaching, and lectures by senior faculty) and barriers (organizational issues related to evening posting and disinterest in have psychiatry as a separate examination subject at the UG level. [5][6][7] The new competency-based undergraduate medical education (CBME) curriculum has been described as a laudable attempt to modernize medical education in India. 8,9 It provides an opportunity to structure the psychiatry curriculum and use optimal teaching-learning methods to equip the Indian Medical Graduate with the requisite knowledge, attitudes, and skills to help patients with psychiatric disorders who seek help in primary care settings.…”
Section: Resultsmentioning
confidence: 99%